Reassessing the Intellectual Legacy of Saifuddin Zuhri (1919-1986): His Contributions to Nationalism and Islamic Moderation - Afifah, Farida Nur (Journal of Islamic History and Manuscript, 2025)
Saifuddin Zuhri was a prominent Indonesian independence activist, Muslim intellectual, and Minister of Religious Affairs whose work significantly shaped discourses on nationalism and Islamic moderation in postcolonial Indonesia. This study reassesses his intellectual legacy by examining his writings, speeches, policies, and organizational activities to understand better his role in fostering the integration of national identity and moderate Islamic values. This research employs a qualitative-historical approach with discourse analysis. Primary sources include Zuhri's publications, speeches, Ministry of Religious Affairs archives, and organizational records from 1920 to 1986. Secondary sources consist of biographies, historical articles, and relevant academic studies. The data were thematically coded to trace narratives on nationalism, tolerance, religious education, and moderation policies. Triangulation of sources and chronological mapping were used to ensure the reliability and validity of interpretations. Findings indicate that Zuhri pursued a dual strategy: (1) reinforcing national identity through inclusive rhetoric positioning Islam as a constructive element of the nation; and (2) promoting moderation via religious education reform, inter-sectarian dialogue, and policies emphasizing social accommodation. The analysis reveals tensions between his reformist ideals and institutional political constraints, yet his influence is evident in Ministry policies and more tolerant community religious practices. This study confirms Zuhri's legacy as relevant to contemporary discourses on moderate Islam in Indonesia and offers a historical model for integrating religion and nationalism.